Pokhorony Stalina (Soviet Union, 1953)
Final tribute to the "Great Leader of Nations". General mourning. Funeral ceremony, Red Square, Moscow. Endless rows of Moscow people, representatives of various Soviet Republics and towns, countries from all over the world on the day of the funeral, March 9, 1953. On the top of the Mausoleum: Viacheslav Molotov, Kliment Vorosilov, Georgii Malenkov, Nikita Khruschev, Lavrentyii Beria. Funeral orations. Laying of the coffin in the Lenin Mausoleum. Closing event: military parade on Red Square, Moscow.
Keywords: Soviet Union